1990
DOI: 10.2136/sssaj1990.03615995005400040017x
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH and Phosphorus and Potassium Uptake by Maize Evaluated with an Uptake Model

Abstract: Plant growth and nutrient uptake by plants have been shown to be affected by soil pH. However, the effects have not been evaluated with a mechanistic uptake model that can evaluate the relative influence of soil pH changes on changes in soil supply parameters that influence predicted P uptake. The objectives of this research were to verify the Barber‐Cushman nutrient‐uptake model under a range of soil pH conditions and to use the model to evaluate the influence of soil pH on the model parameters supplying P an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Regardless of the poorer zinc uptake and changes in the P/Zn ratio, the same one was within limiting values (36-155), in all fertilisation variants, so the average dry matter mass production of this line was higher compared to the preceding one. It could be supposed that unfavourable soil pH reaction caused the poor zinc uptake in our investigations (pH in KCl 7.00) as zinc deficiency occurs at pH 6.5-8.0 (Shuman 1980, Jen-Hshuan Chen andBarber 1990).…”
Section: Resultsmentioning
confidence: 82%
“…Regardless of the poorer zinc uptake and changes in the P/Zn ratio, the same one was within limiting values (36-155), in all fertilisation variants, so the average dry matter mass production of this line was higher compared to the preceding one. It could be supposed that unfavourable soil pH reaction caused the poor zinc uptake in our investigations (pH in KCl 7.00) as zinc deficiency occurs at pH 6.5-8.0 (Shuman 1980, Jen-Hshuan Chen andBarber 1990).…”
Section: Resultsmentioning
confidence: 82%
“…Chen and Barber (1990a) observed that KCl extractable Al increased 3 fold with a pH change from 4.7 to 3.8. High levels of soluble Al harm plants by root pruning and reduced nutrient and water uptake (Chen and Barber, 1990b).…”
Section: Relationship Between Soil Acidity and Phosphorus Chemistrymentioning
confidence: 94%
“…If the level of available P in soil is not adequate for optimum crop growth, phosphate fertilizers must be used to ensure that there are adequate amounts of this nutrient in the solution phase, which is usually variable and unpredictable (Chen and Barber 1990). The formation of insoluble compounds due to soil chemical reactions limits the plant-available P, making phosphate fertilization use efficiency by crops very low (Barber 1984).…”
mentioning
confidence: 99%